Additional Vocational Education During Realization of Federal Projects - V. V. Shekhovtsov; A. S. Plotnikov; O. V. Fetisova (Высшее образование в России)
Breakthrough development of the Russian economy is the global goal which is continuously mentioned by the President in his speeches. Personnel potential of specialists of real sector of the economy has the determinant value for the successful realization of this goal. Specialists with great experience and knowledge in their field of work are of great value. There are a lot of people of pre-retirement age among them. A large number of aged specialists need support to keep in line with the modern trends in work skills improvement in conditions of total automation and digitization because of age and other limitations. VSTU actively takes part in the realization of the Federal project for advanced vocational education of pre-retirement age people and advanced training of companies’ personnel within the Federal project aimed at improvement of work efficiency and employment. To reach the goal the University has developed and implemented several dozen of advanced training programs especially oriented on the most effective and innovative solutions of professional problems by personnel thus contributing to meeting the challenges of the development of the modern economy.